Hubungan Praktik Kesehatan pada Awal Kehidupan dengan Kejadian Stunting pada Balita - Sutrani Rachmawati; Putri Bungsu Machmud; Ratna Djuwita Hatma (Faculty of Public Health, Hasanuddin University, Makassar, 2019)
Banten has the highest prevalence of stunting (29.6%) on Java island and has increased in the last threeyears. Health practice such as early initiation of breastfeeding, exclusive breastfeeding, complementary feeding,and vitamin A was important during child’s early life growth. This study analyzes the association between early lifehealth practice and stunting among children aged 6-23 months in Banten 2017. This study used a cross-sectionaldesign and used secondary data from PSG. The population in this study are the children aged 6-23 months whohad become the sample of Banten Province PSG. Sampling used total sampling and selected 840 children whomet the inclusion criteria. Analysis using chi-square test and multiple logistic regression. There were 25.36% ofthe child were stunting. There was no association between early life health practice and stunting (p=0.111) aftercontrolled by child’s age, number of household, mother’s education and the interaction between health practiceane mother’s education. The interaction test showed that children who got inappropriate health practice and highmother’s education was 0.63 times become stunting (95% CI:0.36-1.11) and children who got appropriate healthpractice and low mother’s education was 1.82 times become stunting (95% CI:0.90-3.67). Health practice was notassociated with stunting, but the interaction variables of health practice and mother’s education was associated.